2022
DOI: 10.1111/tmi.13801
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of paediatric cataract surgery with and without the use of trypan blue

Abstract: Objective: This systematic review was undertaken to answer the research question: "In children with primary cataracts, what are the outcomes (posterior continuous curvilinear capsulorhexis + posterior chamber intraocular lens implantation) of surgery when performed with and without trypan blue staining of the posterior lens capsule?" Methods: An electronic search in six biomedical databases was conducted to identify randomised controlled trials that compared trypan blue with no stain during surgery in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Our comparative results substantiated that staining the internal surface of LECs in vitro has shown a significant detrimental effect on LECs along with the density of cells without producing statistically significant splitting and loss of intactness of the basement membrane in the concentration of 0.06% TB used for 10 s. This indicates that TB is toxic to LECs without disrupting the bag’s integrity. [ 10 11 12 13 14 15 16 17 ] Therefore, our study gives basic research and histomorphology support for future studies by routine in vivo staining of the capsular bag for 10 s and thorough wash before IOL implantation and following the patients for incidence of PCO. Further studies with more sample sizes, lower concentrations of TB, and duration of staining can also be considered to optimize the results.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our comparative results substantiated that staining the internal surface of LECs in vitro has shown a significant detrimental effect on LECs along with the density of cells without producing statistically significant splitting and loss of intactness of the basement membrane in the concentration of 0.06% TB used for 10 s. This indicates that TB is toxic to LECs without disrupting the bag’s integrity. [ 10 11 12 13 14 15 16 17 ] Therefore, our study gives basic research and histomorphology support for future studies by routine in vivo staining of the capsular bag for 10 s and thorough wash before IOL implantation and following the patients for incidence of PCO. Further studies with more sample sizes, lower concentrations of TB, and duration of staining can also be considered to optimize the results.…”
Section: Discussionmentioning
confidence: 77%
“…The types of degeneration seen in our study are one case of cytoplasmic, one case of vacuolar, one case of focal, and three cases of partial degeneration, implying that TB might be responsible for different types of degeneration. [ 10 11 ] In a study by Pankaj Sharma et al .,[ 10 ] it was observed that injecting the TB 0.1% into the capsular bag following phacoemulsification and inserting hydrophilic acrylic IOL reduced PCO. Here in this study, they did the internal staining of the capsule with TB, and our study provides histomorphology evidence for its safe use for the abovementioned purpose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations